Clinical Medical Ethics Landmark Works of Mark Siegler, MD - Roberts, Laura Weiss; Siegler, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This instant gold standard title is a major contribution to the field of clinical medical ethics and will be used widely for reference and teaching purposes for years to come. Throughout his career, Mark Siegler, MD, has written on topics ranging from the teaching of clinical medical ethics to end-of-life decision-making and the ethics of advances in technology. With more than 200 journal publications and 60 book chapters published in this area over the course of his illustrious career, Dr. Siegler has become the pre-eminent scholar and teacher in the field. Indeed his work has had a profound impact on a range of therapeutic areas, especially internal medicine, pediatrics, surgery, oncology, and medical education. Having grown steadily in importance the last 30 years, clinical ethics examines the practical, everyday ethical issues that arise in encounters among patients, doctors, nurses, allied health workers, and health care institutions. The goal of clinical ethics is to improve patient care and patient outcomes, and almost every large hospital now has an ethics committee or ethics consultation service to help resolve clinical ethical problems; and almost every medical organization now has an ethics committee and code of ethics. Most significantly, clinical ethics discussions have become a part of the routine clinical discourse that occurs in outpatient and inpatient clinical settings across the country. This seminal collection of 46 landmark works written by Dr. Siegler with colleagues throughout his career was edited by Dr. Laura Weiss Roberts and by Dr. Siegler. Dr. Roberts is a prominent psychiatric ethicist and physician-scientist as well as a mentee and longtime collaborator of Dr. Siegler. The text is organized around five themes of foundational scholarship: restoring and transforming the ethical basis of modern clinical medicine, the doctor-patient relationship, education and professionalism, end-of-life care, and clinical innovation.With introductory perspectives by a group of renowned scholars in medicine, Clinical Medical Ethics: Landmark Works of Mark Siegler, MD explains the field authoritatively and comprehensively and will be of invaluable assistance to all clinicians and scholars concerned with clinical ethics. .
Part I Restoring and Transforming the Ethical Basis of Modern Clinical Medicine -- 1. An Introduction from Laura Weiss Roberts, M.D., M.A. -- 2. A Perspective from Mark Siegler, M.D. -- 3. A Perspective from Daniel P. Sulmasy, M.D., Ph.D. -- 4. A Perspective from Dana Levinson, M.P.H., Holly J. Humphrey, M.D., and Kenneth S. Polonsky, M.D. -- 5. A Perspective from Jordan J. Cohen, M.D. -- 6. A Perspective from Peter A. Singer, M.D. -- Part II Landmark Works on Clinical Medical Ethics by Mark Siegler, M.D. -- 7. Foundational Scholarship 7.1 Clinical ethics and clinical medicine (1979) -- 7.2 Decision-making strategy for clinical ethical problems in medicine (1982) -- 7.3 An ethics consultation service in a teaching hospital. Utilization and evaluation (1988) -- 7.4 Clinical medical ethics (1990) -- 7.5 Ethics committees and consultants (1990) -- 7.6 Future directions in clinical ethics (1991) -- 7.7 Clinical ethics (1991) -- 7.8 Clinical ethics in the practice of medicine (1996) -- 7.9 Five major themes in bioethics (1997) -- 7.10 The contributions of clinical ethics to patient care (1997) -- 8. The Doctor-Patient Relationship -- 8.1 Searching for moral certainty in medicine: a proposal for a new model of the doctor-patient encounter 1981) -- 8.2 Clinical intuition: a procedure for balancing the rights of patients and the responsibilities of physicians (1981) -- 8.3 The doctor-patient encounter and its relationship to theories of health and disease (1981) -- 8.4 The physician-patient accommodation: a central event in clinical medicine (1982) -- 8.5 Confidentiality in medicine: a decrepit concept (1982) -- 8.6 Medical consultations in the context of the physician-patient relationship (1982) -- 8.7 Metaphors and models of doctor-patient relationships: their implications for autonomy (1984) -- 8.8 The progression of medicine: from physician paternalism to patient autonomy to bureaucratic parsimony (1985) -- 8.9 Learning from our patients: one participant$1 (Bs impact on clinical trial research and informed consent (1997) -- 8.10 The physician-surrogate relationship (2007) -- 9. Education and Professionalism -- 9.1 A legacy of Osler: teaching clinical ethics at the bedside (1978) -- 9.2 Basic curricular goals in medical ethics: the DeCamp conference on the teaching of medical ethics (1985) -- 9.3 Fellowship training programs in clinical ethics (1988) -- 9.4 Development of a teaching program in clinical medical ethics at the University of Chicago (1989) -- 9.5 Internal medicine residents' preferences regarding medical ethics education (1989) -- 9.6 Caring for medical students as patients (1990) -- 9.7 Teaching clinical ethics (1990) -- 9.8 Medical students as patients: a pilot study of their health care needs, practices, and concerns (1996) -- 9.9 What and how psychiatry residents at ten training programs wish to learn about ethics (1996) -- 9.10 Clinical ethics teaching in psychiatric supervision (1996) -- 9.11 Training doctors for professionalism: some lessons from teaching clinical medical ethics (2002) -- 10. End-of-Life Care -- 10.1 Pascal's wager and the hanging of crepe (1975) -- 10.2 Critical illness: the limits of autonomy (1977) -- 10.3 Brain death and live birth (1982) -- 10.4 Against the emerging stream: should fluids and nutritional support be discontinued? (1985) -- 10.5 Euthanasia: a critique (1990) -- 10.6 Elective use of life-sustaining treatments in internal medicine (1991) -- 10.7 Intimacy and caring: the legacy of Karen Ann Quinlan (1993) -- 10.8 The rise and fall of the futility movement (2000) -- 11. Clinical Innovation 11.1 Ethical issues in growth hormone therapy (1989) -- 11.2 Orthopedic surgeons' attitudes and practices concerning the treatment of patients with human immunosuppressive virus infection (1989) -- 11.3 Ethics of liver transplantation with living donors (1989) -- 11.4 Bone marrow transplantation for sickle cell disease; a study of parents$1 (Bdecisions (1991) -- 11.5 Ethical justification for living liver donation (1992) -- 11.6 Transplantation of liver grafts from living donors into adults: too much, too soon (2001) -- 11.7 Elective surgical patients as living organ donors: a clinical and ethical innovation (2009) -- Appendix.s
Keywords: Medicine; Internal medicine; Cardiology; Endocrinology; Neurology; Medicine & Public Health; Internal medicine; Neurology; Cardiology; Endocrinology